A new species of genus Eulimnadia Packard, 1874 (Branchiopoda: Spinicaudata: Limnadiidae) from India with an updated key for some Indian species - Padhye, Sameer M.; Rabet, Nicolas; Kulkarni, Mihir R.; Pagni, Marco (Zootaxa, 2018)
We describe a new species of Eulimnadia, Eulimnadia bondi sp. nov., from the state of Goa, India. This is the 8th species to be described from the country and first from this state. This species differs from all other Indian species in having unique egg morphology–cylindrical egg with dilated borders at both ends and a specific internal eggshell structure. Specimens showed intra-population morphological variation as observed in other species from the genus. Eulimnadia bondi sp. nov. egg resembles the South American E. colombiensis and the Australian E. australiensis. These species are however distinguished on egg morphological details and by some morphological characteristic of adults. Based on the available information, we present an overview of the distribution of the different Indian Eulimnadia species and an updated identification key based on egg morphology.